(untitled) (Journal of Parents and Teachers, 2014)
Through experiences and activities of Artistic Education and Psychomotricity, students get to know better the environment around them and they get a more functional learning. It provides pleasure and a playful component that drives children to want to learn. The article explains some examples of how to do this task.